ACCESS model: a step toward an empowerment model in global health education - Kalyesubula, Robert; Sadigh, Mitra; Okong, Bernard; Munana, Richard; Weswa, Ivan; Katali, Estherloy A.; Sewanyana, James; Levine, Janice; Sadigh, Majid (Frontiers in Education, 2023)
The approaches to global health (GH) partnerships are as varied as the programs available across the globe. Few models have shared their philosophy and structure in sufficient detail to inform a full spectrum of how these collaborations are formed. Although contributions from low- to middle-income countries (LMICs) have markedly grown over the last decade, they are still few in comparison to those from high-income countries (HICs). In this article, we share the African Community Center for Social Sustainability (ACCESS) model of GH education through the lenses of grassroots implementers and their international collaborators. This model involves the identification and prioritization of the needs of the community, including but not limited to healthcare. We invite international partners to align with and participate in learning from and, when appropriate, becoming part of the solution. We share successes, challenges, and takeaways while offering recommendations for consideration when establishing community-driven GH programs.